Conservative management of congenital bronchial atresia: The Bambino Gesù children's hospital experience. Issue 7 (31st March 2021) - Zarfati, Angelo; Voglino, Valerio; Tomà, Paolo; Cutrera, Renato; Frediani, Simone; Inserra, Alessandro
Abstract: Introduction: Congenital bronchial atresia (CBA) is a rare airway malformation. No management guidelines exist because of limited evidence: treatment, surgical or conservative, is based on consensus and opinion. Objective: To review the experience of a pediatric tertiary center and provide additional data about nonsurgical management of CBA and its outcomes after a structured follow‐up, and to help formulate appropriate evidence‐based guidelines. Methods: A retrospective analysis of clinical, radiological, surgical, and pathological data of all pediatric patients with suspicion of CBA referred to the surgical department of the Bambino Gesù children's hospital of Rome between December 2013 and 2019, along with a review of the literature. Results: Among the 18 children initially included in the study, 2 were lost to follow‐up after radiological diagnosis, 4 underwent surgery for radiological suspicion of other pulmonary malformations. The final population is composed of 12 conservatively managed patients. At the end of the follow‐up (median: 29 months, range 3–61), 1 patient (8%) was symptomatic. Conclusion: Conservative management for CBA appears to be safe. Surgery should be reserved for patients with symptomatic or complicated cases.